Natural Antioxidants: Innovative Extraction and Application in Foods - Loizzo, Monica Rosa; Sanches-Silva, Ana Teresa (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Natural Antioxidants: Innovative Extraction and Application in Foods compiles comprehensive information and recent findings on the extraction of antioxidants from different natural resources and investigates their application in food. The book focuses on different sources of natural antioxidants such as the Hypochaeris and Hyoseris species, pomegranate seed oil, thyme, hemp, coriander, olive mill wastewaters, the edible mushroom Hericium erinaceus, Brewer's spent grain, broccoli byproducts, cardoon, and Norway spruce bark. Moreover, the effect of different treatments such as blanching, microwave exposure, roasting, and enzymatic browning on the phytochemical content and bioactivity of the extracts is also addressed. Readers will find valuable insights into the impact of extraction methodologies on the bioactivity of the extracts, along with an understanding of the vast potential of natural extracts for the quality of food products. Readership Food and nutrition researchers, health professionals, nutritionists, and food science and chemistry students